Curcumin protects against testis-specific side effects of irinotecan - Uyanik, O.; Gurbuz, S.; Ciftci, O.; Oguzturk, H.; Aydin, M.; Cetin, A.; Yucel, N. (Verduci Publisher, 2021)
OBJECTIVE: Irinotecan (IR/CPT-11) is a semisynthetic, water-soluble derivative of the alkaloid camptothecin. It is a topoisomerase I group antineoplastic drug commonly used for the treatment of many cancer types, although it has side effects in tissues such as the testis. Curcumin (CRC) is a polyphenol compound produced from the Indian saffron root; it is used as food colouring and food flavouring. This study examined the testis-specific side effects of IR and the ability of CRC to protect against these side effects. MATERIALS AND METHODS: Forty male Sprague-Dawley rats were used in our study (n = 10). The rats were randomly divided into the following four groups: control, IR, IR + CRC, and CRC. IR 10 mg/kg/day was administered intraperitoneally and CRC 100 mg/kg was administered orally. Blood and testicular samples were collected from rats in all four groups on day 30 after drug administration. Histological, biochemical, and spermatological analyses were conducted. RESULTS: Testis tissue and blood samples were collected from the four groups. Tissue samples from the control and CRC groups demonstrated normal histological appearance on light microscopy. The IR group exhibited the following findings: vascular congestion in the tunica albuginea layer; tubular degeneration and vascular congestion in the interstitial area; oedema, vacuolisation, and luminised cells in the seminiferous tubule: and cells that temporarily stopped dividing at any stage of division in the seminiferous tubule epithelium. In the IR+CRC group, histopathological damage was significantly reduced by CRC treatment. Biochemical analysis showed that the level of thiobarbituric acid reactive substance (TBARS) was significantly increased in the IR group, compared with the other groups. CRC treatment significantly decreased this IR-mediated increase in TBARS level, and the TBARS level in the IR + CRC group approached the level observed in the control group. IR treatment caused significant decreases in glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) levels. However, CRC administration tended to ameliorate the decreases in GSH, SOD, CAT, and GPx levels. CONCLUSIONS: In this study, IR had some toxic effects in rat testis tissue: these effects were ameliorated by CRC treatment. Further studies are warranted to confirm our results.
Keywords: Irinotecan; Testis; Curcumin; Rat; SN-38